PENGARUH SUMBER PENGETAHUAN EKTERNAL TERHADAP TYPE INOVASI : SEBUAH TINJAUAN BERBASIS PELAKU PASAR DAN SCIENCE BASED ACTORS (STUDI EMPIRIS PADA UMKM DI YOGYAKARTA) - Siti Nursyamsiah; Saiful Hidayat (Fakultas Ekonomi Universitas Bangka Belitung, 2020)
The research aims to determine the influence of external knowledge sources based on market actors and science actors on the types of innovations including product innovation, process innovation, market innovation and organizational innovation in innovating SMEs food and beverage at D. I Yogyakarta. This research is based on 60 samples obtained from the dissemination of questionnaires directly and through Google form. To analyzed data, this study utilized a logistic regression model with SPSS 23. The findings show that the external knowledge source of market base actors has significant effect on 4 types of innovation. However, the best prediction is shown in Model 1 that is market base actors to product innovation. While analysis of external knowledge sources of Science based actors shows there is no influence on 4 types of innovations, either on models 1 to model 4. Analysis of the control variables also showed no significant influence on innovation. Therefore, the age difference and size of the company in SMEs are not important factors in innovating. The results of this study contribute to the development of innovation in SMEs.